USING THE METHODOLOGY FOR ASSESSING THE EFFECTIVENESS OF THE IMPLEMENTATION OF ELECTRONIC DOCUMENT MANAGEMENT IN EDUCATION - Kornuta В. А. (Journal of Information Technologies in Education (ITE), 2016)
A feasibility assessment of the implementation of electronic document management systems is considered in the article. The necessity of the use of analysis workflow system methods with an intuitive description of the process of working with documents is justified. The uses of a card table to describe the sequence of work with documents and detail the quantitative characteristics of the documents flow are proposed. Business processes’ description of the organization in the form of card tables allowed doing the organization’s description of any scale on one hand in a wellstructured aspect, on the other hand – in a natural form of verbal description. Native description gives a possibility to fill in the table with the assistance of outside experts as well as by the customer organization’s staff, independently of the competence level in the development of information systems. The calculating algorithm of the time and consumables for document management is developed. The using of expert estimates method for complexity of operations with documents is developed. The form of presentation of the calculation results, easy for justifying automation, technical and material support of staff jobs and determination of the appropriate access rights is developed. The calculations of spending by means of spreadsheets are invited. The results of calculations allow making decisions to the state as well as to the amount of work employees and to establish financial and material indexes of investments efficiency. The results of the application of techniques in the teaching process are described.Key words: electronic document; feasibility study; analysis workflow